The Illusion of the “Reverse Kissinger” - Preradović, Nikola (Political Life, 2025)
The renewed great power competition has intensified debates on possible strategies of the United States toward the other two major powers in the international system, Russia and China. One approach that has been gaining popularity, particularly with Donald Trump’s return to the White House, is the “reverse Kissinger” strategy. Drawing on the analogy with President Richard Nixon’s diplomacy and his most influential foreign policy advisor, Henry Kissinger, in the early 1970s—when the restoration of U.S.-China relations weakened the Soviet Union—this approach envisions improving U.S. relations with Russia in order to separate Moscow from Beijing and limit China’s growing power. Relying on a comparative method, the paper examines differences between the original context of this approach and its potential contemporary application. The theoretical framework employed is the balance of threat, which highlights fundamental differences in the perception of security challenges in the modern U.S.–China–Russia triangle compared to the U.S.–USSR–China triangle of the early 1970s. Unlike that stage of the Cold War, when Beijing identified Moscow as its main threat, today both powers perceive Washington’s policy as their central challenge, which has enabled the formation of their strategic partnership. Moreover, tensions caused by the war in Ukraine and Russia’s growing economic dependence on China represent additional obstacles to the application of this strategy. Under such circumstances, the “reverse Kissinger” should be seen as an illusion based on faulty analogical reasoning.